Tarhib Ramadhan dan Dinamika Masjid Komunitas: Penguatan Spiritual Komunitas Muslim Indonesia di Jepang - Mia Fitriah Elkarimah; Zainal Arifin Madzkur (Zad Al-Ummah: Jurnal Pengabdian Masyarakat, 2026)
This community service program aims to strengthen the spiritual readiness and religious understanding of Indonesian Muslim communities in Japan in preparation for the month of Ramadan through a series of mosque-based activities. The activities were carried out using a participatory approach through thematic lectures, Qur’an recitation, shalawat, sharing sessions on the experiences of Muslim migrants, and question-and-answer sessions led by speakers from academic and religious circles who understand the socio-cultural context of Japan. The results show a high level of enthusiasm among participants, reflected in attendance, attentiveness during the sessions, and active participation in discussions on Ramadan worship practices in workplace, campus, and family settings. This series also strengthened scholarly and institutional networks between PCINU Japan, local mosque committees, and universities in Indonesia, and reinforced the function of mosques as a “homecoming space” and a center for consolidating Islam Nusantara in a non-Muslim-majority country. The Tarhib Ramadan program model and the dynamics of these community mosques have the potential to be replicated in other Indonesian Muslim communities abroad as an effort to enhance religious literacy, Ramadan spirituality, and social cohesion among the diaspora.